2016
DOI: 10.1002/ejic.201501110
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Catalytic Route for Alkyn­ylgermanes

Abstract: Abstract:We report a new one-pot, iridium(I)-catalyzed direct method for the synthesis of alkynyl-substituted germanium compounds with various functional groups from commercially available reagents. More than 25 compounds were obtained and spectroscopically characterized. Moreover, detailed DFT cal-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Marciniec has reported that catalyzed treatment of terminal alkynes with iodotrimethylsilane (or iodotrimethylgermane) leads to the efficient synthesis of silylacetylenes and germylacetylenes, respectively. A series of silylacetylenes 557 (Scheme 232) and germylacetylenes 558 Further research has shown that cheaper and more readily available chlorosilanes 559 or chlorogermanes 560 can be used as reaction partners. The synthetic method consists of an in situ generation of iodosilanes in a reaction with NaI or KI.…”
Section: Borylation Of C−h Bondsmentioning
confidence: 99%
See 3 more Smart Citations
“…Marciniec has reported that catalyzed treatment of terminal alkynes with iodotrimethylsilane (or iodotrimethylgermane) leads to the efficient synthesis of silylacetylenes and germylacetylenes, respectively. A series of silylacetylenes 557 (Scheme 232) and germylacetylenes 558 Further research has shown that cheaper and more readily available chlorosilanes 559 or chlorogermanes 560 can be used as reaction partners. The synthetic method consists of an in situ generation of iodosilanes in a reaction with NaI or KI.…”
Section: Borylation Of C−h Bondsmentioning
confidence: 99%
“…DFT computations suggest that the reductive elimination of germylacetylene is the rate-limiting step of germylation. 560 Still, further studies are needed to account for many details of the mechanism.…”
Section: Borylation Of C−h Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, unlike alkynylsilanes, alkynylgermanes have just begun to meet the criteria of useful reagents in organic synthesis. Here, the synthetic arsenal for the formation of sp C-Ge bonds mainly relies on the stoichiometric reaction between moisture-sensitive halogermanes with metal acetylides or the use of expensive transition metal complexes (Ruvinylgermanes/alkynylgermanes [28][29][30] , Ir-chlorogermanes/iodo-germanes 31,32 ). Very recently, an outstanding B(C 6 F 5 ) 3 -catalyzed cross-dehydrogenative germylation of terminal alkynes with triethylgermanium hydride was reported by the Schoenebeck group 33 .…”
mentioning
confidence: 99%